Growth dynamics in regional systems of technological activities - A SVAR approach - Matthias Duschl; Thomas Brenner (Philipps-University Marburg, Department of Geography, 2013)
This paper analyses the causal relationships in regional technological systems within a structural vector autoregression (SVAR) framework. Applying a data-driven identification strategy based on Independent Component Analysis, it shows how the regional growth dynamics of economic, research, innovation and educational activities affect each other instantaneously and over time in five different industries. Referring to the type of industry and its knowledge base, expectations are derived on how industry-specific growth processes unfold. Knowledge on the causal relations among the various activities in such regional technological systems is of utmost relevance to the design and implementation of efficient policy instruments.
Keywords: C33; O30; R11; 330; regional growth; SVAR; non-normality; innovations; universities; R&D; regional technological systems